The Introduction of Transnational Armed Conflicts into International Humanitarian Law - Calleja, Gabriel Stephen R. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
Under international humanitarian law ("IHL"), which limits the effects of armed conflicts, common classifications of armed conflicts have long been in use. Today, however, an improvement to the existing framework is called for because there are now cases of armed conflicts that are not classifiable as either international armed conflicts or non-international armed conflicts under IHL. This article seeks to introduce a new type of armed conflict termed "transnational armed conflict" which comprises armed conflicts that do not fall under a either category and which have the following characteristics: (1) the parties involved are not all States; (2) the armed conflict does not fall under a war of national liberation; and (3) the armed conflict is not limited to the territory of any one State. Not recognizing such armed conflicts under IHL means that there will be no regulation of the fighting and no special protections given to the people caught up in these armed conflicts. This article recommends that a new Convention be agreed upon recognizing and applying to transnational armed conflicts, (1) recognizing of all the basic principles applicable under IHL, (2) relating to prohibitions or restrictions of use of certain types of weapons, and (3) reaffirming the Martens clause.
Keywords: International Law (Armed Conflicts)